Electrochemical removal of levofloxacin using conductive graphene/polyurethane particle electrodes in a three-dimensional reactor. (May 2020) - Guo, Cuicui; Liu, Haiyang; Wang, Chengzhi; Zhao, Jianchen; Zhao, Wenjun; Lu, Nan; Qu, Jiao; Yuan, Xing; Zhang, Ya-nan
Abstract: The conductive polyurethane/polypyrrole/graphene (CPU/PPy/Gr) particle electrode was prepared by an in-situ oxidative polymerization method and used as particle electrodes to degrade levofloxacin (LEV) in a three-dimensional electrode reactor. The prepared CPU/PPy/Gr electrode was characterized systematically and the effects of initial pH, initial LEV concentration, aeration volume, voltage, and electrolyte concentration on the degradation efficiency were investigated. Results showed that more than 90% LEV was degraded and the energy consumption was 20.12 kWh/g LEV under conditions of pH 7, 6 V voltage, 2.0 L/min aeration volume, 20 mg/L initial LEV concentration, and 7 mM concentration of electrolyte (Na2 SO4 ). A possible electrochemical oxidation pathway of LEV by the CPU/PPy/Gr electrode was proposed. In addition, the biotoxicity of LEV and its oxidation products was calculated using ECOSAR (Ecological Structure Activity Relationships) program in EPISuite. Toxicity evaluation using luminescent bacteria showed that the toxicities of some intermediates were higher than the parent compound. But the toxicity of degradation processes for LEV was effective decreasing. A possible reactive mechanism in the three-dimensional reactor was also recommended. In brief, the prepared CPU/PPy/Gr particle electrode constitutes an insight into the promising practical application in the wastewater treatment. Graphical abstract: Image 1 Highlights: CPU/PPy/Gr 3D particle electrode was prepared by in-situ oxidative polymerization. Hydroxyl radical played an important role in the degradation process of LEV. The hybrid toxicity showed an initial increase and later decrease trend over time. The overall toxicity of LEV degradation system was effectively reduced.